Differences in the profile of postoperative complications in patients undergoing breast augmentation and mastopexy with prosthesis - Daronch, Oona Tomiê [UNESP]; Marcante, Renata Fernanda Ramos [UNESP]; Neto, Aristides Augusto Palhares [UNESP] (Thieme, 2023)
Introduction: Breast augmentation is one of the most performed procedures in Plastic Surgery worldwide. Mastopexy with prosthesis is also a widely performed procedure reserved for other patient profiles. Many complications can be avoided when studying risk factors for unfavorable outcomes. Method: This is a retrospective study carried out through the analysis of medical records of patients who underwent primary breast augmentation and mastopexy with breast implants from January 2018 to December 2020. Results: Of the 112 patients who underwent mammoplasty with the implant during the study period, 76 patients underwent primary breast augmentation (67.86%), and 36 underwent mastopexy with breast implant (32.14%). Patients undergoing mastopexy had a higher average age compared to those undergoing breast augmentation (p<0.001) and had smaller volumes of breast implants (p=0.002). The most common complications in both groups include surgical wound dehiscence, more common after mastopexy with prosthesis. Conclusion: Breast augmentation performed as a single procedure has a higher rate of complications when compared to breast augmentation performed individually. However, the greater number of early complications observed with the combined procedure is the sum of the two distinctly individual procedures and not an exponential increase.
Diferenças no perfil de complicações pós-operatórias em pacientes submetidas a mamoplastia de aumento e mastopexia com prótese
Keywords: Breast; Intraoperative complications; Mammaplasty; postoperative complications; Reconstructive surgical procedures